Cd2+ Sorption Alterations in Ultisol Soils Triggered by Different Engineered Nanoparticles and Incubation Times - Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The progressive influx of engineered nanoparticles (ENPs) into the soil matrix catalyses a fundamental transformation in the equilibrium dynamics between the soil and the edaphic solution. This all-encompassing investigation is geared towards unravelling the implications of an array of ENP types, diverse dosages and varying incubation durations on the kinetics governing Cd2+ sorption within Ultisol soils. These soils have been subjected to detailed characterizations probing their textural and physicochemical attributes in conjunction with an exhaustive exploration of ENP composition, structure and morphology. To decipher the intricate nuances of kinetics, discrete segments of Ultisol soils were subjected to isolated systems involving ENP dosages of 20 and 500 mg ENPs·kg−1 (AgNPs, CuNPs and FeNPs) across intervals of 1, 3 and 6 months. The comprehensive kinetic parameters were unveiled by applying the pseudo-first-order and pseudo-second-order models. At the same time, the underlying sorption mechanisms were studied via the intra-particle diffusion model. This study underscores the substantial impact of this substrate on the kinetic behaviours of contaminants such as Cd, emphasizing the need for its consideration in soil-linked economic activities and regulatory frameworks to optimize resource management. © 2023 by the authors.